Efeitos socioeconômicos da pandemia do novo coronavírus: estudo de casos múltiplos no Brasil, Portugal, Colômbia, Israel, Moçambique e Nigéria (2020/2021) - Brito, Daniela Belchior (2021)
The crisis generated by the COVID-19 virus pandemic hit cities in different ways, creating new problems and intensifying existing ones, as well as encouraging and catalyzing solutions for urban planning aimed at quality of life and sustainability. Therefore, this research aimed to identify the vulnerabilities and opportunities facing the crisis by COVID-19 for urban planning in Brazil, Colombia, Portugal, Israel, Mozambique and Nigeria. In this way, a bibliographical review was carried out and, consequently, the elaboration of an interview script to analyze how the effects influenced the daily lives of the citizens of São Paulo (Brazil), Medellín (Colombia), Porto (Portugal), Haifa (Israel), Maputo (Mozambique) and Abuja (Nigeria). The nature of the research is qualitative and the multiple case study method was used. Data analysis occurred through data triangulation, content analysis techniques using the computer program Iramuteq and discussed based on the overview obtained from each city. The results indicated that the predominant economic activities in each location can influence the resilience capacity, which is also related to the use of different technologies, contributing to the survival of businesses and the supply of society in times of pandemic. Therefore, it is important to diversify these activities, in addition to adopting measures to contain the pandemic adapted to each socioeconomic context, considering their specificities. The importance of government management in order to restore trust in institutions was highlighted, which was related to the perceived social engagement in the face of the adopted measures. This demonstrates the need to seek solutions to provide less favored populations with greater accessibility to a better quality of life and access to public services.